The Handbook of Neuroprotection - Jain, Kewal K.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2011)
Neuroprotection has been placed on a firm scientific basis during the past decade due to an improved understanding of the molecular basis of neurological diseases and the knowledge that treatment of neurological disorders should not be merely symptomatic but preventative against the progression of the underlying disease, as well as regenerative.  The Handbook of Neuroprotection serves as a comprehensive review of neuroprotection based on knowledge of the molecular basis of neurological disorders. Neuroprotective effects of older, established drugs, as well as new drugs in development, are well documented in this detailed volume, featuring the most cutting-edge and innovative methods currently in use.   In-depth and authoritative, The Handbook of Neuroprotection features a compendium of vital knowledge aimed at providing researchers with an essential reference for this key neurological area of study.
Introduction -- Neuroprotective Agents -- Neuroprotection in Cerebrovascular Disease -- Neuroprotection in Traumatic Brain Injury -- Neuroprotection in Spinal Cord Injury -- Neuroprotection in Neurodegenerative Disorders -- Neuroprotection in Parkinson's Disease -- Neuroprotection in Alzheimer's Disease -- Neuroprotection in Huntington's Disease -- Neuroprotection in Amyotrophic Lateral Sclerosis -- Neuroprotection in Miscellaneous Neurological Disorders -- Neuroprotection of the Optic Nerve and the Retina -- Neuroprotection during Anesthesia and Surgery -- Future Prospects of Neuroprotective Therapies.
Keywords: Neurosciences; Neurology .; Neurosciences; Neurology